Pengaruh Return On Assets (Roa), Liquidity Funding Ratio (Lfr), Non Performing Loan (Npl), dan Capital Adequacy Ratio (Car) terhadap Penyaluran Kredit pada Bank BUMN yang Terdaftar di BEI Periode Tahun 2013 – 2017 - Achmad Agus Yasin Fadli (Business Management Analysis Journal (BMAJ), 2019)
This study aims to determine the effect of Return on Assets (ROA), Liquidity Funding Ratio (LFR), Non Performing Loan (NPL) and Capital Adequacy Ratio (CAR) on lending. The objects of this research are PT Bank Negara Indonesia (Persero) Tbk, PT Bank Rakyat Indonesia (Persero) Tbk, PT Bank Tabungan Negara (Persero) Tbk, and PT Bank Mandiri (Persero). This research was conducted during the period 2013 - 2017. The method of analysis used in this study is multiple linear regression. The results showed that ROA, LFR, and CAR were negatively related to lending. Whereas NPL has a positive effect on lending. The implication of the research results is that in order to increase lending, it must reduce ROA, LFR and CAR and increase the NPL value.